2012
DOI: 10.3389/fnhum.2012.00186
|View full text |Cite
|
Sign up to set email alerts
|

Punishment sensitivity modulates the processing of negative feedback but not error-induced learning

Abstract: Accumulating evidence suggests that individual differences in punishment and reward sensitivity are associated with functional alterations in neural systems underlying error and feedback processing. In particular, individuals highly sensitive to punishment have been found to be characterized by larger mediofrontal error signals as reflected in the error negativity/error-related negativity (Ne/ERN) and the feedback-related negativity (FRN). By contrast, reward sensitivity has been shown to relate to the error p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 80 publications
1
16
1
Order By: Relevance
“…The current study also failed to find a correlation between FRN amplitude following Losses and ratings of punishment sensitivity, as indicated by BIS scores, in either the PG or HC group, which is in contrast to previous research that examined this relationship using traditional ERP quantification methods (Balconi and Crivelli, 2010;De Pascalis et al, 2010;Santesso et al, 2011;Unger et al, 2012;Van den Berg et al, 2011). This was perhaps due to the fact that the relationship between the FRN and BIS scores was only quantified at Fz in the current study, and not at fronto-central (Santesso et al, 2011;Unger et al, 2012), central (De Pascalis et al, 2010), or centro-posterior (Balconi and Crivelli, 2010) sites, as in prior studies.…”
Section: The Relationship Between Psychophysiological and Personalitycontrasting
confidence: 85%
See 1 more Smart Citation
“…The current study also failed to find a correlation between FRN amplitude following Losses and ratings of punishment sensitivity, as indicated by BIS scores, in either the PG or HC group, which is in contrast to previous research that examined this relationship using traditional ERP quantification methods (Balconi and Crivelli, 2010;De Pascalis et al, 2010;Santesso et al, 2011;Unger et al, 2012;Van den Berg et al, 2011). This was perhaps due to the fact that the relationship between the FRN and BIS scores was only quantified at Fz in the current study, and not at fronto-central (Santesso et al, 2011;Unger et al, 2012), central (De Pascalis et al, 2010), or centro-posterior (Balconi and Crivelli, 2010) sites, as in prior studies.…”
Section: The Relationship Between Psychophysiological and Personalitycontrasting
confidence: 85%
“…Impulsivity has been found to be strongly associated with problem gambling (see van Holst et al, 2010 for a review); however, the few studies that have investigated self-reported sensitivity to reward and punishment in problem gamblers have reported mixed results (Goudriaan et al, 2006;Loxton et al, 2008). Research on the relationship between individual differences in reward and punishment sensitivity and psychophysiological indicators of incentive processing in healthy controls has shown individuals who score higher on self-reported punishment sensitivity measures also display higher FRN amplitudes following unfavourable feedback (Balconi and Crivelli, 2010;De Pascalis et al, 2010;Santesso et al, 2011;Sato et al, 2005;Unger et al, 2012), and that individuals who report higher reward sensitivity also demonstrate greater P300 amplitudes following positive feedback (Van den Berg et al, 2011); however, this relationship has not been examined in problem gamblers. Due to the potential of using self-report measures as screening instruments in the identification of individuals at risk of problem gambling, it is worthwhile examining whether these subjective measures correlate with objective neural responses.…”
Section: The Relationship Between Personality Measures and Psychophysmentioning
confidence: 94%
“…We used a probabilistic learning task previously devised by Eppinger et al (2008) and used by Bakic, Jepma, De Raedt, and Pourtois (2014)), as well as by Unger et al (2012). After a fixation cross of 250 ms duration, and a blank screen (250 ms), a visual stimulus (S) was presented for 500 ms on each trial against a white homogenous background on a 17-inch computer screen.…”
Section: Probabilistic Learning Taskmentioning
confidence: 99%
“…In this study, we tested a well-defined cohort of treatment resistant MDD patients (with high level of anhedonia) and compared their learning performance and RPE signals (using conventional EEG/ERP methods) during a probabilistic learning task (Eppinger, Kray, Mock, & Mecklinger, 2008;Unger, Heintz, & Kray, 2012) to a group of age and education level matched healthy controls (HCs). We assessed if MDD could impair internal (ERN) and/or external (FRN) RPE signals, and whether it would be associated with decreased RL (at the behavioral level) compared to HCs in this task (Pizzagalli et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In a comment to this study, Tops and Koole (2012) extended the discussion of the findings arguing that traits related to higher task engagement predict ERN amplitude. Unger et al (2012), on the other hand, reported a positive association between higher punishment sensitivity and higher FRN amplitudes, independent of feedback validity, which at the same time appeared to be related to poorer behavioral learning performance.…”
mentioning
confidence: 97%